(f-g)(x) = x²+6x - (7-x)
(f-g)(x) = x² + 6x - 7 + x
(f-g)(x) = x² + 7x - 7
(f-g)(9) = 9² + 7*9 - 7
(f-g)(9) = 81 + 63 - 7
(f-g)(9) = 137
Given the expression
![\frac{3}{5} (3y+15)](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B5%7D%20%283y%2B15%29)
The expression that is equivalent to the given expression is given by:
(48a^3 + 32a^2 + 16a) / 4a = ?
48a^3 / 4a = 12a^2
32a^2 / 4a = 8a
16a / 4a = 4
so
(48a^3 + 32a^2 + 16a) / 4a = 12a^2 + 8a + 4
Answer is D. 12a^2 + 8a + 4
Answer:
The measure of the angles are 40 degrees and 50 degrees
Step-by-step explanation:
Let
x ----> the measure of one angle in degrees
y ----> the measure of the complementary angle in degrees
we know that
If two angles are complementary, then their sum is equal to 90 degrees
so
----> equation A
we have that
----> equation B
Substitute equation B in equation A and solve for y
![(y-10)+y=90\\2y-10=90\\2y=100\\y=50](https://tex.z-dn.net/?f=%28y-10%29%2By%3D90%5C%5C2y-10%3D90%5C%5C2y%3D100%5C%5Cy%3D50)
Find the value of x
![x=50-10=40](https://tex.z-dn.net/?f=x%3D50-10%3D40)
therefore
The measure of the angles are 40 degrees and 50 degrees
Answer:
Step-by-step explanation:
-22